Designing a 3D Animation-Based Promotional Video for Sublimation Fabric Product of Asietex - Maya Silva; Hamdan Hamdan; Sunardi Sunardi (Brilliance: Research of Artificial Intelligence, 2025)
PT. Asietex Sinar Indopratama is a vertically integrated textile manufacturer specializing in the full production cycle—from spinning yarn to producing finished fabrics. The majority (85%) of its top-line fabric output is composed of cotton or rayon, while the remaining portion utilizes polyester materials. In line with its commitment to ongoing innovation, the company has launched a high-performance Direct-to-Garment (DTG) and sublimation printing division. This division offers enhanced print clarity, vivid color expression, and superior resistance to repeated washing. Such technological advancements have enabled PT. Asietex to respond efficiently and flexibly to market needs in both large-scale and custom textile applications, particularly in the fashion and home décor sectors.The primary objective of this study is to explore how 3D visual presentation techniques influence consumer interest and sales performance for the company’s textile products. The research method included designing 3D fabric product models using Blender 3D software and creating an animated promotional video that showcases key features and advantages of the sublimated fabric line. This promotional content was distributed through various online marketing channels.To assess the impact of the visualization, feedback was collected from a group of potential customers who viewed the animation, and comparative sales data were analyzed before and after the campaign. Survey findings indicate that 85% of participants considered the video to be highly descriptive and useful in understanding the product. Moreover, 78% expressed heightened curiosity and interest in the sublimation fabric after viewing the video.